2010
DOI: 10.1017/s0007114510000280
|View full text |Cite
|
Sign up to set email alerts
|

Effect of glycomacropeptide fractions on cholecystokinin and food intake

Abstract: Glycomacropeptide (GMP) is the hydrophilic 64-amino acid C-terminal glycopeptide released into cheese whey when k-casein is cleaved by chymosin. GMP exists as a mixture of different glycoforms due to the carbohydrates sialic acid (N-acetylneuraminic acid, NeuNAc), galactose (Gal), galactosamine and glucosamine attached by O-glycosidic linkages. GMP reportedly stimulates the release of cholecystokinin (CCK), which may promote satiety. The objectives of the present study were to manufacture three glycoforms of G… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 41 publications
(16 citation statements)
references
References 21 publications
1
15
0
Order By: Relevance
“…These differences are possibly related with the hydrophilicity of the different peptides. Although hydrophilicity of WPC hydrolysate was not characterized, literature reports that GMP is highly hydrophilic (Keogh et al, 2010), while lactoferrin presents both hydrophobic and hydrophilic areas in its conformation (Lu et al, 2005).…”
Section: Moisture Content and Water Solubilitymentioning
confidence: 99%
“…These differences are possibly related with the hydrophilicity of the different peptides. Although hydrophilicity of WPC hydrolysate was not characterized, literature reports that GMP is highly hydrophilic (Keogh et al, 2010), while lactoferrin presents both hydrophobic and hydrophilic areas in its conformation (Lu et al, 2005).…”
Section: Moisture Content and Water Solubilitymentioning
confidence: 99%
“…Supportive evidence however is lacking [106,107]. In an isoenergetic study of whey protein, whey protein plus GMP, whey protein-derived alpha-lactalbumin (α-lac), casein and non-dairy soy protein, it was α-lac that was shown to suppress intake relative to the other fractions [111], whilst in a study comparing various forms of GMP no differential effects on intake were reported [112]. In a recent study of overweight women from our laboratory we also found no differential effect of GMP on energy intake [113] when we gave matched beverages containing 25 g of whey protein concentrate, GMP, beta-lactoglobulin (β-lac) and colostrum-derived whey protein, although greater fullness was induced by β-lac [113].…”
Section: Introductionmentioning
confidence: 99%
“…Test meal intake was not different by preload: GMP alone was not considered by the authors as critical in pre-meal whey-induced satiety; however, it may have a role in compensatory intake regulation. Other authors found no significant difference in CCK levels, neither subjective measures of satiety nor in food intake between treatments at the given preload level, whatever the degree of glycosylation of the GMP (Keogh et al, 2010).…”
Section: Feeding (Appetite Satiety) and Obesitymentioning
confidence: 87%